2023
DOI: 10.1007/s10886-023-01423-4
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Conversion Leads to Detoxification of Salicortin-like Chemical Defenses (Salicortinoids) in Lepidopteran Specialist Herbivores (Notodontidae)

Abstract: Lepidopteran specialist herbivores of the Notodontidae family have adapted to thrive on poplar and willow species (Salicaceae). Previous research showed that Cerura vinula, a member of the Notodontidae family occurring throughout Europe and Asia, uses a unique mechanism to transform salicortinoids, the host plant’s defense compounds, into quinic acid-salicylate conjugates. However, how the production of this conjugates relates to the detoxification of salicortinoids and how this transformation proceeds mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…If larger structural modifications to salicinoids occurred, they thus probably led to decomposition of the salicinoid‐like structure by the cleavage of ester bonds (Boeckler et al, 2016). This is in line with other studies that showed that salicinoids are largely metabolised when ingested by insect herbivores (Boeckler et al, 2011, Ruuhola et al, 2001; Schnurrer & Paetz, 2023).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…If larger structural modifications to salicinoids occurred, they thus probably led to decomposition of the salicinoid‐like structure by the cleavage of ester bonds (Boeckler et al, 2016). This is in line with other studies that showed that salicinoids are largely metabolised when ingested by insect herbivores (Boeckler et al, 2011, Ruuhola et al, 2001; Schnurrer & Paetz, 2023).…”
Section: Resultssupporting
confidence: 92%
“…to negatively affect polyphagous caterpillars (Boeckler et al, 2016), it would be interesting to test whether L. populi has some mechanisms that allow to circumvent these effects as reported for other host-plant specialists associated with Salicaceae (Schnurrer & Paetz, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information coupled with the comparable ECD curve with those of 1 – 3 determined the absolute configuration of 6 as 1′ S , 2′ R , 3′ S , 4′ S , 5′ R , 1″ S , which was corroborated further by TDDFT-ECD analysis (Figure ). The absolute configurations of compounds 4 and 5 were assigned as the same as that of 6 , as deduced from their consistent 1D NMR data of fragment B and similar tendencies of the ECD curves, and supported by TDDFT-ECD analysis of 4 (Figure ), as well as their shared biosynthesis from salicin derivatives. , …”
Section: Resultssupporting
confidence: 63%
“…The absolute configurations of compounds 4 and 5 were assigned as the same as that of 6, as deduced from their consistent 1D NMR data of fragment B and similar tendencies of the ECD curves, and supported by TDDFT-ECD analysis of 4 (Figure 3), as well as their shared biosynthesis from salicin derivatives. 49,50 Compounds 7 (salixteroside G) and 8 (salixteroside H) were initially obtained as pale-yellow gum. Their molecular formulas were determined as C 23 H 30 O 12 based on the HRESIMS and 13 C NMR data, implying nine IHDs.…”
Section: Characterization Of Compounds Salixteroside a (1mentioning
confidence: 99%